Conversion factors of the temperature effect on the shear strength of adhesively-bonded steel joints - Pasternak, Hartmut; Sahellie, Samer (Journal of Civil Engineering and Management, 2016)
This paper presents the investigations on lap shear galvanized steel joints bonded by two structural adhesives (acrylic and epoxy) with two thicknesses of the bondline. The effect of the temperature on the shear strength of the adhesives when the joints are short-term-loaded is the main objective of the investigations. The partial factors of the limit states as well as the conversion factors that cover the use conditions and circumstances and particularly the temperature influence, within a temperature range from –20 °C to +40 °C, are proposed. These factors are proposed by two methods commonly used in the respective standards; the direct evaluation method and prediction model-based method. A comparison between the results obtained by these methods is presented.